Енергетичний спектр електронів у тришаровій гетеросистемі із самоорганізованими дефектно-деформаційними структурами - Peleshchak, R.M.; Kuzyk, O.V.; Dan’kiv, O.O. (Publishing house "Academperiodika", 2012)
Equations, which enable the electron energy spectrum in a three-layer heterosystem containing a cluster of point defects in a quantum well to be calculated, have been derived in the framework of the deformation potential method. The dependence of the electron energy difference between the first excited andground states on the average concentration of point defects of the stretching-center type has been studied for various effective electron masses in a nanocluster material.